2020
DOI: 10.1073/pnas.1920193117
|View full text |Cite
|
Sign up to set email alerts
|

15-Epi-LXA 4 and 17-epi-RvD1 restore TLR9-mediated impaired neutrophil phagocytosis and accelerate resolution of lung inflammation

Abstract: Timely resolution of bacterial infections critically depends on phagocytosis of invading pathogens by polymorphonuclear neutrophil granulocytes (PMNs), followed by PMN apoptosis and efferocytosis. Here we report that bacterial DNA (CpG DNA) and mitochondrial DNA impair phagocytosis and attenuate phagocytosis-induced apoptosis in human PMNs through Toll-like receptor 9 (TLR9)-mediated release of neutrophil elastase and proteinase 3 and subsequent down-regulation of the complement receptor C5aR. Consistently, Cp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 58 publications
7
109
0
Order By: Relevance
“…These findings supported also by results of animal studies [ 225 , 226 , 227 ], may suggest a potential role for EPA and DHA in reducing the lung injury supporting the resolution of inflammation, probably via the production of SPMs [ 207 ]. However, further trials are needed to support this hypothesis.…”
Section: Omega-3 Fatty Acidssupporting
confidence: 61%
“…These findings supported also by results of animal studies [ 225 , 226 , 227 ], may suggest a potential role for EPA and DHA in reducing the lung injury supporting the resolution of inflammation, probably via the production of SPMs [ 207 ]. However, further trials are needed to support this hypothesis.…”
Section: Omega-3 Fatty Acidssupporting
confidence: 61%
“…They found a 19% reduction in individuals taking a daily or weekly dose without bolus doses and no benefit with bolus dosing. Among those receiving a daily or weekly dose, they observed a 25% reduction for those with baseline 25(OH)D levels ≥25 nmol/L (12 ng/mL) and a 70% reduction for those with baseline levels <25 nmol/L [23]. They concluded that daily or weekly vitamin D supplementation protected against ARI overall and that it was safe.…”
Section: Nutritional Impact On Immunitymentioning
confidence: 98%
“…This could be very important in the context of severe COVID-19 which manifests as uncontrolled inflammation, the so-called cytokine storm [18,19], linked with acute respiratory distress syndrome (ARDS). A number of the SPMs formed from EPA and DHA have been shown in animal models to both protect against and resolve acute lung injury and ARDS [20][21][22][23][24]. Nutritional formulas containing antioxidants and rich in EPA and DHA have been used in several human trials of patients with ARDS.…”
Section: Nutritional Impact On Immunitymentioning
confidence: 99%
“…Whilst we found that specific lipid mediators were elevated in response to the GPR40 agonist: these were RvD3, lipoxins, RvE1 and RvE3 ( Figure 4 ). Notably, RvD3, lipoxins and RvE1 are effective in enhancing the clearance of E. coli infection ( 28 ), bacterial pneumonia ( 29 ), and resolution of UV-killed E. coli in human blisters ( 30 ). Systematic analysis of pro-resolving lipid mediator profiles in septic patients with acute respiratory distress syndrome (ARDS) indicated that the amount of circulating 10 S ,17 S -diHDHA (PDX) at day 3 was a better predictor of ARDS development than the APACHE II score ( 31 ), further supporting the role of SPM in regulating host responses during infections.…”
Section: Discussionmentioning
confidence: 99%